Prediksi Harga Mata Uang Kripto XRP Menggunakan Metode Deep Learning LSTM Dan GRU - Muhammad Syahrul Ramadhan A.S. Dapubeang; Edwin U. Malahina (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to predict the price of the XRP cryptocurrency using deep learning methods, specifically Long Short-Term Memory (LSTM) and Gated Recurrent Unit (GRU). Given that high price volatility can pose challenges for investors, this study analyzes and compares the effectiveness of the two models in processing complex time series data. In addition, this study also evaluates the influence of external factors such as price volatility and market sentiment on prediction accuracy. It is hoped that the results of the study can provide valuable insights for investors and traders in formulating more appropriate investment strategies, as well as contributing to the development of new methods in financial data analysis and crypto price prediction, so that this study is relevant to both academics and practitioners in the financial industry